Suppression of Bacterial Leaf Spot by Green Synthesized Silica Nanoparticles and Antagonistic Yeast Improves Growth, Productivity and Quality of Sweet Pepper - Eman F. A. Awad-Allah; Amany H. M. Shams; Amira A. Helaly (Plants, 2021)
Plants are challenged with many kinds of biotic stresses caused by different living organisms, which result in various types of diseases, infections, and damage to crop plants and ultimately affect crop productivity. Plant disease management strategies based on current approaches are necessary for sustainable agriculture. A pot experiment was carried out under greenhouse conditions to evaluate the potential of green synthesized silica nanoparticles (SiO2-NPs) and antagonistic yeast (Saccharomyces cerevisiae) against pepper bacterial leaf spot disease, caused by Xanthomonas vesicatoria. In addition, to assess their efficacy and suppressive effects in reducing disease severity and improving sweet pepper growth, productivity, and quality. Results revealed that the combination of BCA (5%) and SiO2-NPs (150 ppm) was the most effective treatment for reducing disease severity and improving vegetative growth characters, mineral contents (N, P, K, Ca, Mg, and Si in leaves), as well as stimulating polyphenol oxidase (PPO) activity of sweet pepper leaves at 90 days from transplanting, while also at harvesting time enhancing sweet pepper fruit yield quality parameters significantly. In conclusion, green synthesized silica nanoparticles combined with antagonistic yeast have the potential to suppress a bacterial leaf spot disease with ecologically-sound management, while also boosting sweet pepper growth, productivity, and quality.